Pendeteksi dini dan penjejak kendaraan yang datang dari jarak jauh dengan pendeteksi referensi titik hilang untuk lampu lalu lintas adaptif - Yoanda Alim Syahbana; Dodi Zulherman; Yokota Yasunari (JURNAL INFOTEL, 2023)
Real-time traffic monitoring is essential for the operation of an adaptive traffic lighting system and plays a significant role in decision-making, particularly signaling in roadworks. When only one lane is accessible due to temporary road blockage, early detection of oncoming vehicles is crucial to minimize bottlenecks near the traffic light that could result in congestion and accidents. This research aimed to enhance the detection and tracking of traffic at a distance from the traffic light. We utilized the vanishing point as a reference for detection and calculated the region of interest. We implemented the proposed method on twelve traffic surveillance videos and evaluated the system performance based on how quickly it could detect incoming traffic compared with the R-CNN method. The proposed method detected target vehicles in an average of 17.75 frames, while the R-CNN method required an average of 63.36 frames. Moreover, the proposed method’s precision depends on the number of pixel orientations used to estimate the vanishing point and the definition of the region of interest. Therefore, the proposed method for enhancing the safety and reliability of an adaptive traffic light system is reliable.